Crossover of thermal expansion from positive to negative by removing the excess fluorines in cubic ReO3-type TiZrF7−x. Issue 19 (18th April 2018) - Yang, Cheng; Zhang, Yugang; Bai, Jianming; Qu, Bingyan; Tong, Peng; Wang, Meng; Lin, Jianchao; Zhang, Ranran; Tong, Haiyun; Wu, Ying; Song, Wenhai; Sun, Yuping
Abstract : We realize the crossover from PTE to NTE by removing the excess fluorines in TiZrF7− x . Abstract : We report the crossover of the coefficient of thermal expansion (CTE) from positive to negative by withdrawing the excess fluorines in ReO3 -type TiZrF7− x ( x = 0, 0.5 and 1) compounds. The average volumetric CTE between 300 K and 623 K changes from 8.07 ppm K −1 for x = 0, to 0.66 ppm K −1 for x = 0.5 and finally to −6.09 ppm K −1 for x = 1. After withdrawing the excess fluorines, the lattice expands and the edge-sharing polyhedra partially transform to corner-sharing ones, which enhances the transverse vibrations of fluorines and thus accounts for the crossover of CTE. Moreover, these compounds are narrow-gap semiconductors with the energy gap decreasing with x . NTE may also be achievable in other fluorine-excess cubic fluorides by removing the excess fluorines, which opens up a new avenue for exploring the NTE in fluorides.